PERBEDAAN HOJODOUSHI ～ている DAN ～てある DALAM KALIMAT BAHASA JEPANG - Rahmawati, Anita; Rini, Elizabeth; Wiyatasari, Reny (Japanese Literature, 2016)
My research problems are : 1. How are the structure and meaning of auxiliaryverb „–teiru‟ and „–tearu‟? 2. How are the similarities and differences betweenauxiliary verb „–teiru‟ and „–tearu‟?.The purpose of this research are : 1. To describe the structure and meaning ofauxiliary verb “–teiru” and “–tearu”. 2. To describe the the similarities anddifferences between auxiliary verb “–teiru” and “–tearu”. The research methodused is Agih method. In analyzing the data, this research used descriptive analysistechnique.The result of this research show that the auxiliary verb “-teiru‟ and “-tearu” areto express the meaning of condition and both are express resultatif aspect. Thedifference are : 1. auxiliary verb –teiru express the result of certain action. Thespeaker merely wants to describe the appearance of situation and auxiliary verb–teiru can used intransitive verb and transitive verb . 2. auxiliary verb –tearudescribes an action that is done with a certain objective in mind and auxiliaryverb –tearu only used transitive verb.